Determination of the working length in root canal treatment using bisecting angle technique (Mustansiria Dental Journal, 2004)
Bisecting angel technique si used for viewing (30) selected vital teeth from patients who attended a dental clinic for extracting those teeth mostly because of pain. The selected teeth are upper and lower central incisors, canines, and premolars. Asize 20 file si inserted ni each tooth, with different length as follows: 19mm which are calibrated after they had extracted using a ruler. It si found that when the difference between file end and the apex of the tooth is not exceed (0.5 mum,) the bisecting angle technique give an accurate estimation for working length of the tooth, otherwise this technique is not recommended to be used in root canal treatment because of the incorrect estimation that is gained when the difference is more than (0.5 mm).